(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
A promising area of the national economy of Ukraine is the development of hotel and restaurant business. All over the world, the hotel and restaurant business is developing quite rapidly. In 2017, the number of foreigners visiting Ukraine increased by about 1 million people - to 14.5 million. According to the World Travel & Tourism Council, the number of jobs threatened by the Covid-19 pandemic could reach 75 million. In Europe, up to 10 million jobs in the field of travel and tourism are at risk, a loss of almost 552 billion dollars. In Ukraine, the losses are estimated at 0.5 million jobs. The article establishes that the hotel and restaurant business suffered significant losses during the Covid-19 period. It is proved that in modern conditions it is necessary to develop development strategies that will counteract internal and external risks. The main strategies of hotel and restaurant business development in the period of Covid-19 are systematized. In particular, two groups of development strategies have been identified: the strategy of maintaining a positive image in the market and the strategy of overcoming the negative consequences of the Covid-19 pandemic. It is proposed to create smart cities within hotel and restaurant complexes. There are 10 signs on the basis of which it is possible to assert the existence of smart cities within the hotel and restaurant business. The strategy of development of hotel and restaurant business should be formed taking into account modern tendencies of development. To do this, it is necessary to develop approaches that would reduce the level of risk caused by the emergence of negative customer expectations. To do this, a marketing and sales strategy must be used. The main role will be played by corporate culture, which will be the core of future strategic changes. Important for implementation is the innovation strategy, the implementation of which should take place through the creation of smart cities within the hotel and restaurant complex. This approach minimizes contact with the external environment and promotes a positive impression of service quality.